Trees and their seed networks: The social dynamics of urban fruit trees and implications for genetic diversity - Rimlinger, A.; Avana, M.-L.; Awono, A.; Chakocha, A.; Gakwavu, A.; Lemoine, T.; Marie, L.; Mboujda, F.; Vigouroux, Yves; Johnson, V.; Vinceti, B.; Carrière, S.M.; et al. (Public Library of Science, 2021)
Trees are a traditional component of urban spaces where they provide ecosystem services critical to urban wellbeing. In the Tropics, urban trees’ seed origins have rarely been characterized. Yet, understanding the social dynamics linked to tree planting is critical given their influence on the distribution of associated genetic diversity. This study examines elements of these dynamics (seed exchange networks) in an emblematic indigenous fruit tree species from Central Africa, the African plum tree (Dacryodes edulis, Burseraceae), within the urban context of Yaoundé. We further evaluate the consequences of these social dynamics on the distribution of the genetic diversity of the species in the city. Urban trees were planted predominantly using seeds sourced from outside the city, resulting in a level of genetic diversity as high in Yaoundé as in a whole region of production of the species. Debating the different drivers that foster the genetic diversity in planted urban trees, the study argues that cities and urban dwellers can unconsciously act as effective guardians of indigenous tree genetic diversity.